Popular Diabetes Apps and the Impact of Diabetes App Use on Self-Care Behaviour: A Survey Among the Digital Community of Persons With Diabetes on Social Media - Kebede, Mihiretu M.; Pischke, Claudia R. (Frontiers in Endocrinology, 2019)
Introduction: Evidence on whether diabetes apps improve diabetes self-care behavior in real-world settings is still limited. This study aimed to identify popular diabetes applications (apps) and to investigate the association of diabetes app use and other factors with cumulative self-care behavior. Methods: From November 2017 to March 2018, we conducted a web-based survey with persons 18 years of age and above. We recruited respondents via diabetes Facebook groups, online patient-forums and targeted Facebook advertisements (ads). Data on participants’ demographic, clinical, and self-management characteristics, as well as on self-care behavior and characteristics of the diabetes apps use were collected. Self-care behavior was measured using a licensed version of the Summary of Diabetes Self-care Activities (SDSCA) questionnaire. Questions regarding diabetes smartphone applications were adapted from the Mobile Application Rating Scale. To identify popular diabetes apps, users were requested to list all apps they use for diabetes self-management. Two sample t-test and multiple linear regression stratified by type of diabetes were performed to examine associations between app use and self-care behavior. Results: 1052 respondents with type 1 and 630 respondents with type 2 diabetes mellitus (DM) entered the survey. More than half, 549(52.2%), and one third, 210(33.3%), of respondents with type 1 and 2 DM, respectively, reported using diabetes apps for self-management. “mySugar” and continuous glucose monitoring apps, such as “Dexcom”, “Freestyle Libre”, and “Xdrip+” were some of the most popular diabetes apps. In both respondent groups, the cumulative self-care behavior score was significantly higher among diabetes app users (compared to non-users) and scores for three individual self-care components, namely “blood glucose monitoring”, “general diet”, and “physical activity” were significantly higher among diabetes app users than among non-users. After adjusting for confounding factors, diabetes app use increased the cumulative self-care score by 1.08(95%CI: 0.46-1.7) units among persons with type 1 DM and by 1.18(95%CI: 0.26 – 2.09) units among persons with type 2 DM, respectively. Conclusion: For both, persons with type 1 and type 2 diabetes, using diabetes apps for self-management was positively associated with self-care behavior. Our findings suggest that apps can support changes in lifestyle and glucose monitoring in these populations.